Mediating Wasathiyah Islamic with Da’wah in the Public Sphere - Islam, Nurul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article focuses on mediating da'wah content through YouTube, packaged in the Islamic concept of wasathiyah. The rampant phenomenon of da'wah content leads to radicals & fundamentals, and even terror on social media causes public unrest. The public space is a space for equality, the emergence of discussions of public issues, and turning public activities and points into inclusive cultural commodities. This study uses a qualitative research method through social semiotic analysis’ Halliday of the object of research on the Jedanulis (based on specific content YouTube) and content analysis of the audience's comments to determine the behavior of users using Netlytic. This is done to determine the audience’s response (as a social media user) to the communicator Husain Jafar Alhadar. The representation of wasathiyah da'wah concludes with a point, which is a source. Ustaz is an actor who conveys divine teachings and promotes a positive image of Islam through inclusive practice in the public sphere. What they get as a message becomes a mirror for the listener. Ustaz is the message itself. Whether faith is good or bad is determined mainly by them. That Ustaz, including Ulama, is not mocking the ummah but inviting the ummah.